The Prognostic Implication of Coronary Artery Calcification in Patients with Atrial Fibrillation - Chih-Weim Hsiang; Wen-Yu Lin; Cheng-Hsiang Lo; Chun-Yu Liang; Tsung-Kun Lin; Chun-Hsien Hsieh; Jia-En Chen; Wen-Cheng Liu (Journal of Medical Sciences, 2023)
Background: Coronary artery calcification (CAC) is a well-validated parameter reflecting the extent of subclinical atherosclerosis. Atherosclerosis manifestations are commonly presented in atrial fibrillation (AF) patients. Nevertheless, the long-term cardiovascular risks in AF patients with concomitant CAC are limited. Aim: The aim of this study is to identify the prognostic impact of CAC in patients with AF. Methods: A total of 646 eligible patients who underwent noncontrast coronary computed tomography (nCCT) from January 2012 to December 2018 were evaluated and retrospectively followed up for 2 years. The patients were assessed for cardiovascular outcomes, including nonfatal myocardial infarction, nonfatal stroke, late coronary revascularization, major adverse cardiovascular event (MACE), and total coronary and total composite events, by a multivariable Cox regression hazards model with adjusting for significant confounding factors. Results: AF patients with severe CAC (CAC score [CACS] >400 Agatston units) had significantly higher risks of composite cardiovascular outcomes, including MACEs (adjusted hazard ratio [HR]: 57.18, 95% confidence interval [CI]: 2.28–1434.41, P = 0.014), total coronary events (adjusted HR: 16.48, 95% CI: 1.21–224.15, P = 0.035), and total composite events (adjusted HR: 26.35, 95% CI: 2.45–283.69, P = 0.007), than sinus rhythm patients without CAC. Moreover, severe CAC in AF patients was a significant predictor of total composite events (adjusted HR: 59.1, 95% CI: 2.16–1616.33, P = 0.016). Conclusion: Severe CAC in AF patients may cause significantly higher cardiovascular risks, highlighting the role of nCCT in determining CACs for early risk evaluation to facilitate aggressive risk modification and thereby to prevent subsequent cardiovascular events. Further, large, prospective studies are needed to validate the impact of CAC in patients with AF.